The Polar Cultural Heritage as a Tourism Attraction: A Case Study of the Airship Mooring Mast at Ny-Ålesund, Svalbard - Roura, Ricardo (Téoros, 2009)
This paper explores the use of narratives in the transformation of historic sites in the polar regions into attractions and consumable tourism products. The analysis is based on a case study of visitation to the airship mooring mast built at Ny-Ålesund, Svalbard, for the 1926 “Amundsen-Ellsworth-Nobile Transpolar Flight” of the airship Norge. The questions addressed in this paper are: How does cultural heritage in the polar regions operate as a tourist attraction? What is the role of tourism narratives in creating a tourism attraction? Direct observations constituted the main research method. Based on Dean MacCannell (1976) and Neil Leiper (1990), a tourism attraction is a system comprising a tourist or human element; a nucleus or central element; and a marker or informative element. Tourism narratives enable the different elements of the tourism attraction system to “click” together into a coherent whole. Through narratives, the mast becomes a place of significance and a symbolic marker of the North Pole and polar exploration. The application of this approach to other sites in Antarctica and Svalbard is discussed.